Titus Coan family papers - Coan, Titus, 1801-1882.
Family and general correspondence, diaries, journals, books by Coan entitled Adventures in Patagonia (1880) and Life in Hawaii (1882), articles, and printed matter, chiefly 1832-1882, relating to the Coan (Coyne) family, to Coan's missionary work in Patagonia (1833-1834), Hilo, Hawaii (1834-1882), and the Marquesas Islands (1860, 1867), and to religion and missionary work in general. Persons represented include Coan's first wife, Fidelia Church Coan (1810-1872), his daughter, Harriet Fidelia Coan (1839-1906), his son, Samuel Latimer Coan (1846-1887), and his sister-in-law, Maria Church Robinson. Some of the articles and printed matter reflect Coan's interest in volcanoes, including observations of Kilauea on the island of Hawaii. Includes a biography (1884) of Coanby his second wife, Lydia Bingham Coan. Correspondents include Sophie Madeleine Du Pont, Chester Smith Lyman, and Mary and Sarah Oliphant.
Presbyterian clergyman and missionary.
Collection material in English, with Hungarian.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Coan, Fidelia Church, -- 1810-1872.; Coan, Harriet Fidelia, -- 1839-1906.; Coan, Lydia Bingham; Coan, Samuel Latimer, -- 1846-1887.; Coyne family; Du Pont, Sophie -- Correspondence; Lyman, Chester Smith, -- 1814-1890 -- Correspondence; Oliphant, Mary -- Correspondence; Oliphant, Sarah -- Correspondence; Robinson, Maria Church; Missions -- French Polynesia -- Marquesas Islands; Missions -- Hawaii -- Hilo; Missions -- Patagonia (Argentina and Chile); Presbyterian Church -- Missions; Religion; Volcanoes -- Hawaii; Kilauea Volcano (Hawaii); Clergy; Missionaries